Clinicopathological characteristics and prognosis of primary appendiceal stromal tumors - Bao Zhang; Guo Liang Zheng; Hai Tao Zhu; Yan Zhao; Zhi Chao Zheng (World Journal of Surgical Oncology, 2018)
Abstract Background Gastrointestinal stromal tumors (GISTs) account for less than 1% of all gastrointestinal tumors. The biological behaviors of GISTs vary from benign to malignant. GISTs are common in the stomach (55.6%) and small intestine (31.8%), but rarely in the rectum, colon (6%), and other sites (5.5%). Currently, the majority of published reports of primary appendiceal stromal tumors (PASTs) are case reports or case series. Methods The PASTs described in this study were identified from a literature review (23 cases) and our center (one case). The relationship between PAST gross types and clinicopathological factors was analyzed and summarized. At the same time, the study also analyzed the related risk factors and survival of PASTs and GISTs. Results Twenty-four cases of PASTs were compared with 254 cases of GISTs from our center. The results showed that there was a significant difference between the two groups in tumor size (P < 0.001), histological type (P = 0.013), CD34 expression (P < 0.001), and DOG-1 expression (P < 0.001). Disease-free survival (DFS) analysis of 11 cases of PASTs and 227 cases of GISTs found that a comparison of 3-year and 5-year DFS was not statistically significant (P = 0.894 and P = 0.846, respectively). In the DFS multivariate analysis, tumor mucosal ulceration, tumor size, and NIH risk classification were independent prognostic factors in 3-year and 5-year DFS. Conclusion In this study, there was no significance in the survival of patients with appendix and gastric stromal tumors, which we hypothesized to be associated with the low sample size and incomplete follow-up records. Based on this, we conclude that the prognosis of primary appendiceal stromal tumors may be better than gastric tumors, but this needs to be confirmed in further prospective studies.